Peningkatan kemampuan mengidentifikasi keberagaman masyarakat Indonesia melalui model pembelajaran Point Counterpoint pada siswa kelas IV sekolah dasar - Dhimas Risang Bramansya; Hasan Mahfud; Matsuri Matsuri (Didaktika Dwija Indria, 2019)
The purposes of this research is to improve the ability to identify the diversity of  Indonesian society through application Point Counterpoint learning model. This research was conducted in fourth grade students of SD N 2 Sidomulyo 2018/2019 school year. Types of this research is Classroom Action Reseacrh. This research conducted with two cycles, each cycles consists of four stages, namely planning, observation,action and reflection. Data analysis techniques use interactive analysis model consisting of data collection,data reduction,data presentation and conclusion. Subject of this study were 38 students and class teacher. Data validity testing technique usescontent validity, sources triangulation and technique triangulation. Pre-action results show all students did not reach minimal completness criteria that is 75. After first cycle is completed, researcher got the data that 20 students pass the minimal completness criteria or the class get classical completness 53% and 47% or 18 students did not pass the criteria.in the second cycle, researcher got  data that 31 srudents pass the criteria with average values 75,4 and got classical completness 81,57%. Conclusion of this study is implementation Point Counterpoint learning model can improve the ability to identify the diversity of Indonesian society in fourth grade studentsSD N 2 Sidomulyo in the 2018/2019 school year.